Analysis of Performance Quality of Administrative Employees at Center for The Development of Quality Assurance of Vocational Education in Building and Electricity Field - Cindy Clara; Usman Jayadi (LAFADZ JAYA Publisher, 2022)
This research is intended to identify the quality of employee activities. This research uses qualitative methods. Information gathering was attempted through monitoring, questioning and documentation. Sourced from questions and answers with administrative employee informants, employees also have self-ability, maximum activity results, activities and enthusiasm in working. The research procedure used in this research is a qualitative descriptive procedure where each information is combined, analyzed and then concluded that the type of research used is qualitative descriptive. The results of this research conclude that the system and rules of the method of removal of state -owned property are in accordance with Regulation of the Minister of Finance No. 83. or PMK. 06 Deed of 2016 on the rules of the method of destruction and destruction of state property as well as the release of elements of the internal regulation system of the ruler in accordance with the Regulation of the Internal Regulation System of the ruler No. 60 of 2008.